O08 Pharmacokinetics of prophylactic and therapeutic fluconazole in preterm neonates. Issue 6 (17th May 2019) - Engbers, A; Flint, RB; Völler, S; Reiss, IKM; Liem, KD; Degraeuwe, PLJ; Andriessen, P; Alffenaar, JWC; Koch, BCP; Simons, SHP; Knibbe, CAJ; Brüggemann, R
Abstract : Introduction: Fluconazole is a first choice drug for neonatal cerebral candidiasis and for prevention of candidemia/invasive candidiasis in neonates. Selection of the optimal neonatal dose is difficult and requires solid multiple dose pharmacokinetic (PK) research to guide dosing decisions. We performed a pharmacokinetic study in preterm neonates who received fluconazole prophylactically or as treatment. Methods: Preterm neonates received fluconazole according to local protocol for either prophylaxis or treatment in 5 different hospitals. Samples were collected on multiple occasions with an opportunistic sampling scheme. Patient characteristics were bodyweight, birthweight, postnatal age (PNA), gestational age (GA), postmenstrual age, gender and weight for age. Population PK modelling was performed using NONMEM V.7.3. Results: In 44 preterm neonates (median (range) GA 25.3 (24.0–31.3) weeks), 153 plasma samples were collected. Median PNA at treatment initiation was 1 (0–59) day, treatment duration 11 (2–67) days and median PNA during treatment 15 (4–60) days. A one-compartment model described the data best, with an estimated clearance (CL) for a neonate of 0.84 kg and PNA of 15 days of 0.0147 L/h (RSE 4.3%, interindividual variability 21.4%) and volume of distribution (Vd ) of 0.815 L (RSE 5.9%). Bodyweight was found to influence both CL and Vd, with exponents of 1.05 (RSE 13.4%) and 1.19 (RSE 22.4%), respectively. Maturation of CL was best described by an exponent of 0.184 on PNA (RSE 34.3%). Conclusion: In this pharmacokinetic study on fluconazole in preterm neonates, CL was influenced by both bodyweight and PNA while Vd was influenced by bodyweight only. These findings imply that initial dosing of fluconazole in preterm neonates should be based on bodyweight and that an increase of the dose with 32% during the first week and with 47% during the first month of life could be necessary because of increasing clearance with PNA. Disclosure(s): Nothing to disclose